PENINGKATAN MENYIMAK ANAK USIA DINI MELALUI CERITA ESTAFET DALAM BERCERITA DI TK ALQURAN YABAS PANYAKALAN KECAMATAN KUBUNG KABUPATEN SOLOK - Rita Mulyeni; Nur Hazizah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Listening is an active process that requires a person to capture information, understand messages, and respond to information conveyed verbally. This research is motivated by the low listening skills of young children, particularly in paying attention to teacher explanations, understanding story content, answering questions, and continuing the storyline. The purpose of this study is to improve listening skills in young children through the use of the relay story method in storytelling activities. The method used in this study was Classroom Action Research (CAR), implemented in two cycles. Each cycle included planning, implementation, observation, and reflection. The research subjects consisted of 13 children aged 5–6 years at the Al-Quran Yabas Panyakalan Kindergarten, Kubung District, Solok Regency. Data collection techniques were conducted through observation, interviews, and documentation. The data obtained were analyzed descriptively quantitatively and qualitatively by comparing the results from each cycle.The results showed that the application of the relay story method in storytelling improved children's listening skills. In Cycle I, the average children's listening skills reached 38%, then increased to 69% in Cycle II. Thus, the relay story method in storytelling is effectively used to improve the listening skills of early childhood children at Al-Quran Yabas Panyakalan Kindergarten, Kubung District, Solok Regency.